2021
DOI: 10.1093/nar/gkab477
|View full text |Cite
|
Sign up to set email alerts
|

smORFer: a modular algorithm to detect small ORFs in prokaryotes

Abstract: Emerging evidence places small proteins (≤50 amino acids) more centrally in physiological processes. Yet, their functional identification and the systematic genome annotation of their cognate small open-reading frames (smORFs) remains challenging both experimentally and computationally. Ribosome profiling or Ribo-Seq (that is a deep sequencing of ribosome-protected fragments) enables detecting of actively translated open-reading frames (ORFs) and empirical annotation of coding sequences (CDSs) using the in-reg… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 69 publications
0
25
0
Order By: Relevance
“…By screening reviews [ 47 , 78 ] and recently published studies [ 38 , 39 , 41 , 42 , 44 ], we found 12 stand-alone Ribo-seq based ORF detection tools (Table 1 ). Additionally, we identified several tools that predict potential ORFs from only RNA-seq (transcriptome) data and included the newest example ( ) for comparison.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…By screening reviews [ 47 , 78 ] and recently published studies [ 38 , 39 , 41 , 42 , 44 ], we found 12 stand-alone Ribo-seq based ORF detection tools (Table 1 ). Additionally, we identified several tools that predict potential ORFs from only RNA-seq (transcriptome) data and included the newest example ( ) for comparison.…”
Section: Resultsmentioning
confidence: 99%
“…also uses the same noise filtering strategy based on a sigmoid curve as . Recently, a modular tool for ORF prediction based on both Ribo-seq and TIS data ( [ 44 ]) was introduced, which incorporates three-nucleotide periodicity information. The first module generates all potential sORF candidates, which can be filtered by Fourier transformation of their Ribo-seq read signal and/or based on a region of interest.…”
Section: Introductionmentioning
confidence: 99%
“…The unallocated space (24 074–24 170) resulted in Prodigal reporting the next downstream CDS starting at 24 091 instead of 24 133 (as in the Ensembl annotation), erroneously including 5' UTR in the predicted CDS. There are now tools to identify putative short ORFs in both prokaryotes and eukaryotes using additional evidence, such as RNA expression data ( Bartholomäus et al , 2021 ; Ji et al , 2020 ; Miravet-Verde et al , 2019 ). Our results suggest that the identification of short and overlapping CDSs cannot be done independently without the potential for unforeseen consequences for annotation accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…CDS prediction, often the first step, is fast, with little user input, but may require augmentation by different methods to supplement the initial predictions. One example is a tool, such as smORFer ( Bartholomäus et al , 2021 ), that specializes in finding short ORFs through the use of RNA-seq, which can detect transcription events under certain environmental conditions. Further examples use sequence conservation scores and homology searches that can use existing database knowledge ( Badger and Olsen, 1999 ; Dunne and Kelly, 2017 ; ÓhÉigeartaigh et al , 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…To date, many tools have been developed to predict ORFs, particularly small ORFs, from RPFs of prokaryotes [ 30 ] and eukaryotes (see review of [ 7 , 15 ]). These tools allocate the translated P-sites or A-sites [ 31 ] according to the positions and offsets of RPFs, thereby determining the translated frame for a given sequence of transcripts.…”
Section: Discussionmentioning
confidence: 99%